2021
DOI: 10.3389/fphar.2021.613211
|View full text |Cite
|
Sign up to set email alerts
|

Bexarotene Impairs Cognition and Produces Hypothyroidism in a Mouse Model of Down Syndrome and Alzheimer’s Disease

Abstract: All individuals with Down syndrome (DS) eventually develop Alzheimer’s disease (AD) neuropathology, including neurodegeneration, increases in β-amyloid (Aβ) expression, and aggregation and neurofibrillary tangles, between the third and fourth decade of their lives. There is currently no effective treatment to prevent AD neuropathology and the associated cognitive degeneration in DS patients. Due to evidence that the accumulation of Aβ aggregates in the brain produces the neurodegenerative cascade characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 101 publications
(147 reference statements)
0
4
1
2
Order By: Relevance
“…In contrast to our observations, previous studies have suggested that RXR agonists rapidly stimulate Aβ clearance, thereby improving cognitive and behavioral deficits in mouse models of AD [54]. Nevertheless, long-term treatment with RXR agonists has not been found to decrease Aβ plaque formation [55,56], thus suggesting a different role of RXR on Aβ plaques during long-term treatment. Furthermore, our in vitro ChIP experiments showed that RXRα, RXRβ, and VDR clearly directly bound the promoters of app and bace1 in HEK293 cells.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our observations, previous studies have suggested that RXR agonists rapidly stimulate Aβ clearance, thereby improving cognitive and behavioral deficits in mouse models of AD [54]. Nevertheless, long-term treatment with RXR agonists has not been found to decrease Aβ plaque formation [55,56], thus suggesting a different role of RXR on Aβ plaques during long-term treatment. Furthermore, our in vitro ChIP experiments showed that RXRα, RXRβ, and VDR clearly directly bound the promoters of app and bace1 in HEK293 cells.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, memory impairments were seen in hypothyroid rats as indicated by a significant decrease in both the number of times they crossed the platform and the average distance in the target zone as well as an increase in the time spent in the opposite target zone compared to the corresponding control rats. The percentage of time spent in each quadrant during the probe test is a measure of spatial memory that is not dependent on the animals' level of activity (Vidal et al, 2021). The present study showed a decline in this type of memory with an increase in the time spent in the opposite zone in rats with hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…Current rodent models of DS have excellent construct validity and exhibit a range of AD relevant phenotypes. Notably, elegant work in preclinical models has already indicated that careful thought is required regarding the use of γ-secretase modulators in people who have DS (Lana-Elola et al, 2021 ), that bexarotene may clear Aβ effectively but also impairs cognitive performance in a DS preclinical model (Vidal et al, 2021 ), and that different vaccination protocols for anti-Aβ studies (Illouz et al, 2019 ) may be required in the context of trisomy of Hsa21.…”
Section: Discussionmentioning
confidence: 99%
“…Aβ is a key target for cognitive decline in AD-DS because it's role is proposed to occur upstream of other changes; other targets have been investigated in the Ts65Dn model, such as estrogen, which may have utility at later stages of disease progression (Hunter et al, 2004b ). Notably, the use of bexarotene, a selective retinoid receptor agonist, to reduce Aβ in the hippocampus of the Ts65Dn mouse, worsened cognitive deficits; likely via an effect on thyroid function (Vidal et al, 2021 ), despite leading to Aβ clearance and improvements in cognitive decline in a model of Aβ accumulation (Cramer et al, 2012 ). Therapeutic targets for AD-DS must take into consideration the affect that trisomy has on AD-pathology and on wider physiology of individuals with DS, and such that effective drugs for AD might not always be suitable for the treatment of AD-DS, because of the specific physiology and co-morbidities of individuals with the condition.…”
Section: Pre-clinical Modeling Of Ad-ds: Mechanistic Insightsmentioning
confidence: 99%